Family Resilience in Facing Social and Educational Challenges Elementary School Children in Rural Communities - Kusnanto, Kusnanto; Silvester, Silvester; Torimtubun, Hendrikus; Jewarut, Siprianus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to describe community perceptions of the challenges and support in children's education in Puteng Village, Teriak District, Bengkayang Regency. Using a descriptive quantitative approach, data were obtained through a closed-ended questionnaire distributed to 50 respondents who met the purposive sampling criteria. The results indicate that the majority of the community experiences serious obstacles in social, economic, and infrastructure aspects that affect children's education. Barriers such as an unsupportive social environment, peer pressure, lack of public facilities, difficult road access, and limited parental education are dominant factors that hinder children's learning process. However, strong resilience was also found in families, demonstrated by the high commitment of parents to continue accompanying and motivating children to be enthusiastic about school. Support from the community, traditional leaders, schools, and the government is still relatively low, so cross-sector synergy is needed to create a more inclusive and equitable education system in remote areas.